2020
DOI: 10.1136/esmoopen-2020-000990
|View full text |Cite
|
Sign up to set email alerts
|

Uveal melanoma-associated cancers revisited

Abstract: BackgroundUveal melanoma (UM) is the most common primary ocular malignancy of adults. A small group of patients was found to express familial predisposition. Moreover, it may be preceded or followed by other malignancies elsewhere in the body. We aim to compare the incidence of UM and other associated cancers and study the factors that may influence each condition.Patients and methodsWe have collected the data from the Surveillance, Epidemiology and End Results database of nine US cancer registries for UM pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Our findings of an increased risk were consistent with a Swedish population study, based on the Swedish Cancer Registry, and two cohort studies, based on data from the Surveillance Epidemiology and End Results (SEER) cancer registry [ 12 , 13 , 22 ]. A previous Danish cohort study from 1995 identified an increased rate of new cancer among males only, but the study relied on registry data only and included all patients with an ocular cancer rather than only patients diagnosed with posterior UM [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings of an increased risk were consistent with a Swedish population study, based on the Swedish Cancer Registry, and two cohort studies, based on data from the Surveillance Epidemiology and End Results (SEER) cancer registry [ 12 , 13 , 22 ]. A previous Danish cohort study from 1995 identified an increased rate of new cancer among males only, but the study relied on registry data only and included all patients with an ocular cancer rather than only patients diagnosed with posterior UM [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…We observed a systematic error in the Danish Cancer Registry, where metastatic uveal melanoma was misclassified as primary cutaneous melanoma with distant metastases. This issue has been previously described by other registry-based studies [ 13 , 22 ]. Thus, in order to avoid coding bias, we excluded all cutaneous melanoma cases which presented with a combined coding of new cutaneous melanoma and metastatic disease.…”
Section: Discussionsupporting
confidence: 54%
“…There are various hypotheses dealing with occurrence of additional primary malignancies in UM patients. Because of common co-existence with cutaneous melanoma and breast cancer many reports direct attention to BAP-1 tumour predisposition syndrome ( BAP1 -TPDS) [ 6 , 7 , 10 , 13 ]. This inherited disorder is associated with an increased risk for numerous tumours, both malignant and benign, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with UM have a 9% increased risk of developing a second malignancy, such as cutaneous melanoma, leukemia, thyroid cancer, kidney tumors, and tumors of other parts of the eye or orbit, compared to healthy individuals. On the other hand, there was an 8% increased risk of developing UM after the first diagnosis of any of these other tumors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%